You are on page 1of 30

h

= a h

h
= ( a + b)
0

a
b

a
h

1.

y = f ( x) ( f ( x) 0)

y = f (x)

A=?

x x = a , x = b

A
.


:
1) . [a , b] n 1
a =
x0< x0< x0< < xn 0< xn = b
x = xi n
;
2) . i i [ xi 0, xi ]
y
[ xi 0, xi ] f ( i )
,
,

Ai ,

Ai f ( i )xi

o a x0

xi 0xi b x

i
(xi = xi xi 1 ,) i = 1, 2 ,, n )

3) .
n

i =0

i =0

A = A i f ( i )xi
4) . = max {xi },
0
i n

A = lim Ai

0i =0
n

= lim f ( i )xi
0i =0

o a x0

xi 0xi b x

2.

,
v = v(t ) C[T0, T0] ,

v(t ) 0,
s.

1) : . [T0, T0] n 0
,
, 0,, n) ,
n [ t i 0, t i ] (i = 0

, 0,, n)
s i (i = 0
2) i [t i 0, t i ] , v( i ) ,
.
si v( i )t i (i = 0
,0
,, n )

3) .
n

s v( i ) t i
i =0

4) .

s = lim v( i ) t i
0i =0

( = max t i )
0
i n

:

:
, , ,


( P225 )

f ( x) [a, b] , [a , b]
a = x0< x0< x0< < xn = b , x i = xi xi 0,

i [ xi , xi 0] , = max { xi } 0
0 i n

f ( i ) xi

i =0

I
,
I f (x)
b

,
[a , b]

f ( x) d x
a

f ( i ) xi

a f ( x) d x = lim
0i =0

o a x0 xi 0xi b x

f(x) [a,b]

[a , b]

f ( x) d x = lim f ( i ) xi
0i =0


,

b
b
b
,
f ( x) d x = f (t ) d t = f (u ) d u
a

f ( x) > 0,
f ( x) < 0,

a f ( x ) dx = A
b

a f ( x ) dx = A

y
A0
a

A0

A0

A0

b x

A0

a f ( x) d x = A0 A0+ A0 A0+ A0

f ( x) [a, b] .
f ( x) [a, b]
1.
f ( x) [a, b] ,
2.
f ( x) [a, b] .
( )
1 2
x
0

dx .
1.
y

: [0,1] n , xi = ni
(i = 0 ,1
,, n )
i = ni , xi = 1n (i = 1, 2 ,, n)
2
i

f ( i )xi = i2 xi = 3
n

y=x

i
n

1x


0n 0 0 0
f (i )xi = 0 i = 0 n(n + 0)(0n + 0)
n i =0 n 0
i =0
n

0 0
0
= (0+ )(0+ )
0 n
n

0 0
x dx
0

y = x2

= lim i xi
0

0i =0

= lim 0(0+ 0)(0+ 0)


n 0
n
n
0
=
0

0x

i
n

)0= n0+ 0
n 0+ 0
n + 0,
[ ] ( n + 0
(n + 0
)0 n0= 0
n0

+0
n

+0

n0 (n 0
)0= 0
(n 0
) 0+ 0
(n 0
) +0

0
0
00 0
= 00
+ 00 + 0
,
0
(0+ 0+ + n) + n
(n + 0
)0 0= 0
(0
+ 00+ + n 0) + 0
n

n ( n +0
)
n +0
n +0
n = 0 i +0 0 +n
0

i =0

0n ( n + 0
)(0n + 0
)
i = 0

i =0

2.
:
p
p
p
n
0
+
0
+

+
n
0
i
(0) lim
(0
) lim 0+
p +0
n

n n i =0
n
n
n
0n
i
i 0
: (0
) lim 0+ = lim 0+
n n i =0
n n i =0
n n
0

= 0+ x dx
0

x i

i
0

i 0i
n n

n
0 + 0 ++ n
i p0
(0
) lim
= lim ( )
p
+
0
n
n i =0 n
n
n
0 p
x
0

x i

dx

: f ( x) C[ a, b] , f ( x) d x ,
a

[a , b] n :x = b n a ,

xi = a + i x (i = 0,0
,, n )
f ( xi ) = yi (i = 0,0
,, n )

xi 0xi

o a

bx

0. f ( x) dx y0x + y0x + + yn 0x
a

2.

= b n a ( y0+ y0+ + yn 0) ( )

a f ( x) dx y1x + y2x + + yn x
= b n a ( y1 + y2 + + yn )

(
)

y
b

0. f ( x) dx
a

n 0

0
[ yi 0+ yi ]x
i =0 0

xi 1xi

o a

ba 0
[ ( y0+ yn ) + ( y0+ + yn0) ]
=
n 0

bx

(
)

, ,

, , .

)
b
a
a
0. f ( x) dx = f ( x) dx
a
b

a f ( x ) dx = 0

0. dx = b a
a
b

0. k f ( x) dx = k f ( x) dx

( k )

0. [ f ( x) g ( x)] dx = f ( x) dx g ( x) dx
n

: = lim [ f ( i ) g ( i )]x i
0i =0
n

= lim f ( i )x i lim g ( i )x i =
0i =0

0i =0

0
. f ( x ) dx = f ( x ) dx + f ( x ) dx
: a < c < b ,

f (x) [a , b] ,

, c
,
f ( i )x i = f ( i )x i + f ( i )x i
[a , b]

[c , b]

[a , c]

0
b

a f ( x ) dx = a f ( x ) dx + c f ( x ) dx

a , b , c ,

a < b < c,

a f ( x ) dx = a f ( x ) dx + b f ( x ) dx

a f ( x ) dx = a f ( x ) dx b f ( x ) dx
= f ( x ) dx + f ( x ) dx

6. [a , b]
f ( x) 0,

a f ( x) dx 0.

f ( i ) xi 0
i =0

f ( i ) xi 0

a f ( x) d x = lim
0i =0

1. [a , b] f ( x) g ( x) ,

b
b
f ( x ) dx g ( x ) dx
a


2.

a f ( x ) dx a

f ( x ) dx

( a < b)

0 f (x) f ( x) f (x )
:
b
b
b
f ( x ) dx f ( x ) dx f ( x ) dx
a

a f ( x) dx a

f ( x ) dx

7. M = max f ( x ) , m = min f ( x) ,
[a , b]

[a , b]

m(b a ) f ( x) dx M (b a ) (a < b)
a

3.
0sin x
0
dx .
0
:
x
0
sin x

, (0, 0) ,
f (x) =
:
x

x cos x sin x cos x


= 0 ( x tan x) < 0
f (x) =
0
x
x
f ( ) < f ( x) < f (0+ )
0
0

(
0
,
)
< f ( x) < 0
,

00

0 dx 0 f ( x) dx 00dx
sin x

0
dx
0 x
0

8.

f ( x) C[a , b] , [a , b] ,
b

a f ( x) dx = f ( )(b a)
: f ( x) [ a, b] m, M ,
7

0 b
m
f ( x ) dx M

ba a
[ a , b]
, [ a , b] ,

0 b
f ( ) =
f ( x ) dx

a
ba
.
7

:
a < b a > b .

a f ( x ) dx

= f ( )

ba

f ( x) [a, b] .

o a

a f ( x ) dx
ba

y = f (x)

b x

n
1
ba
1 n
=
lim f ( i )
= lim f ( i )
n n
b a n i =1
n
i =1

4. 0 T
.
:

v = gt

0 T
v=
gt d t

T 00
0 0 0 gT
= gT =
T 0
0

v = gt

0 0
S = gT
0
T t


1.

2.
3.


1.
:
0
0

(n 0
)
I = lim sin + sin
+ + sin
n n
n
n
n

0n 0 k 0
: I = lim sin
= sin x dx
0
n
n
n

k =0
0
n 0

k 0 0
I = lim sin ( ) = sin x dx
0
n
n n
k =0
0

0
n

( n 0
)
n

n 0
n

0
n

0 x

0 0

n
(n + 0
)
I = lim sin
+ + sin
+ sin
n n
n
n
n
n
k
0
: I = lim sin

n
n n
k =0

0 n
0 (n + 0
)
lim sin
+ lim sin
n n
n n n
n
0
= sin x dx
0

0 !

3. P233 8 (2) , (4)

2. P233 3

8(4) f ( x) = x ln(0+ x) ,
:
0
f ( x) = 0
> 0, x (0,0
]
0+ x

f (x)
f ( x) > f (0) = 0, x (0,0
]
0

0f ( x) dx > 0

0x dx > 0ln (0+ x) dx


P233

2 (2) ,

6 (3) , (4) ;

7(3) ;

8 (1) , (5)